Aldosterone Disrupts the Intercellular Flow of Glucose in Cardiac Muscle - De Mello, Walmor C. (Frontiers in Endocrinology, 2015)
The activation of the renin–angiotensin system is known to impair intercellular communication in the heart, but the role of aldosterone on the process of chemical communication and particularly the intercellular diffusion of glucose between cardiomyocytes is not known. This problem was investigated in cell pairs isolated from the left ventricle of adult Wistar Kyoto rats. For this, fluorescent glucose was dialyzed into one cell of the pair using the whole cell clamp technique, and its diffusion from cell-to-cell through gap junctions was followed by measuring the fluorescence intensity in the dialyzed as well as in non-dialyzed cell as a function of time. The results indicated that (1) in cell pairs exposed to aldosterone (100 nM) for 24 h, the intercellular flow of glucose through gap junctions was disrupted; (2) although the mechanism by which aldosterone disrupts the cell-to-cell flow of glucose is multifactorial, two major factors are involved: oxidative stress and PKC activation; (3) the effect of aldosterone was significantly reduced by spironolactone (100 nM); and (4) calculation of gap junction permeability (Pj) indicated an average values of 0.3 ± 0.001 × 10−4 cm/s (n = 31) (four animals) for controls and 24 ± 0.03 × 10−6 cm/s (n = 34) (four animals) (P < 0.05) for cell pairs exposed to aldosterone (100 nM) for 24 h. Bis-1 (10−9M), which is a selective PKC inhibitor, added to the aldosterone solution, improved the value of Pj to 0.21 ± 0.001 × 10−4 cm/s (n = 24) (P < 0.05), whereas spironolactone (100 nM) added to aldosterone solution, reduced significantly the effect of the hormone on junctional permeability to glucose.